Developing a knowledge platform on value of parks for tourism - Hughes, Michael; Carlsen, Jack (BEST Education Network, 2009)
National Parks and other protected natural areas are a significant point of focus for tourism activity globally. Consequently it is important to understand the values of parks for tourism to assist with effective policy, planning and management of protected areas as conservation reserves and as tourism and recreation resources. The gathering of knowledge to better inform understanding of tourism has been described as the Knowledge Platform. The ideal being that gathering of knowledge about tourism will provide a broader understanding of the parks tourism system as a whole and better inform decision making. This paper reviews a series of 24 parks valuations for tourism between 1991 and 2007, focusing on economic valuations as an example. The intent was to explore whether these valuations had contributed to a greater understanding of parks values in the spirit of the tourism knowledge platform. The parks valuations for tourism seem to have occurred in an ad hoc manner using a wide variety of techniques and expression of value of varying complexity. This has produced a disjointed and occasionally contradictory body of knowledge around economic values of parks for tourism. A coordinated approach to parks valuations for tourism using a single accepted method would greatly improve understanding and assist with parks policy, planning and management.